Deteksi Dini Risiko Sindrom Metabolik melalui Pemeriksaan Kesehatan ASN - Kori Kornelia; Helpi Nelwatri; Renidayati; Heppi Sasmita; Wella Meitri; Hamdani; Arif Paria Musta (CV. CENDIKIA JENIUS INDONESIA, 2026)
This community service activity aimed to conduct early detection of metabolic syndrome risk factors among civil servants, identify their health status based on metabolic parameters, and increase awareness of the importance of routine health check-ups. The method was implemented through comprehensive health examinations, including measurements of blood pressure, body mass index, waist circumference, blood glucose, uric acid, and cholesterol levels among 230 participants, followed by brief individual counseling based on examination results. The activity was carried out through preparation, registration, examination, counseling, and evaluation stages. The results showed that a significant proportion of participants had metabolic risk factors, with obesity prevalence at 46.5%, overweight 18.3%, elevated cholesterol 45.2%, high blood pressure 32.2%, increased uric acid 32.6%, and elevated blood glucose 11.7%. The counseling provided helped participants understand their health conditions and encouraged healthier lifestyle behaviors. In conclusion, health screening is effective in early detection of metabolic syndrome risk factors and in improving awareness of routine examinations as promotive and preventive efforts against non-communicable diseases in the workplace.